BRAF-mutated colorectal cancer: clinical implications for a distinct subset of the disease. (June 2015) - Liang, Jennifer; Khorana, Alok A; Kalady, Matthew F
SUMMARY : Colorectal cancer (CRC) is many diseases, with each case defined by the underlying genetic and molecular changes of that particular tumor. The heterogeneity of CRC emphasizes the need to understand this disease within the context of genetic subsets. BRAF mutations mark a subpopulation that arises through the serrated pathway to carcinogenesis. This subset of cancers is associated with unique clinical and histopathologic characteristics. BRAF -mutated CRCs have a worse prognosis compared with their wild-type counterparts, and may not be as responsive to chemotherapy. Target therapies specifically against BRAF and its related signaling pathways are under both scientific and clinical investigation. This article highlights the clinical relevance of the subset of BRAF -mutated CRCs.